Anorexia Nervosa and Somatoform Dissociation: A Neglected Body-Centered Perspective. Issue 1 (1st January 2023) - Longo, Paola; Marzola, Enrica; Martini, Matteo; Amodeo, Laura; Abbate-Daga, Giovanni
ABSTRACT: Dissociation in anorexia nervosa (AN) is common (literature reported 29% of dissociative disorders in eating disorders) and higher in patients with binge-purging AN (BP-AN) than in those with restricter AN (R-AN). However, the distinction between somatoform (SomD) and psychoform dissociation (PsyD) is understudied. We aimed to assess the differences in PsyD and SomD, eating-related, general, and body-related psychopathology, and childhood trauma between subtypes of AN. Then, we attempted to describe a subgroup of patients with AN with marked SomD comparing them to patients without SomD, also controlling the results for PsyD and AN subtypes. Inpatients with AN (n = 111; 109 women and 2 men) completed self-reported questionnaires evaluating dissociation, eating-related, body-related, and general psychopathology, and childhood abuses. Patients with BP-AN reported higher SomD and PsyD and a more severe clinical picture than those with R-AN. The SomD-group (n = 41) showed higher eating concerns, trait-anxiety, body-related variables, and sexual/physical abuse compared to the no-SomD group (n = 70), independently of AN subtype and PsyD symptoms. Results described particular features of patients with AN and SomD. Data, clinically, suggest a careful assessment, for both SomD and PsyD, especially when a history of bodily-impacting trauma is present, potentially fostering dissociation-informed interventions.